Simulation of long-term direct aerosol radiative forcing over the arctic within the framework of the iAREA project. (1st January 2021) - Markowicz, K.M.; Lisok, J.; Xian, P.
Abstract: This paper presents the climatology of aerosol optical properties and radiative forcing over the Arctic obtained within the framework of the iAREA (impact of absorbing aerosols on radiative forcing in the European Arctic) project. The presented data were obtained from the Navy Aerosol Analysis and Prediction System (NAAPS) and the Fu-Liou radiative transfer model. NAAPS was used to simulate particle concentration and aerosol optical depth (AOD) at 1 ° × 1 ° spatial resolution. Direct aerosol radiative forcing (ARF) was calculated for clear-sky and all-sky conditions based on NAAPS reanalysis (with AOD assimilation) and satellite observations of surface and cloud properties. Long-term data (2003–2015) from NAAPS show that anthropogenic and biogenic aerosol, as well as sea salt, make the most important contribution to total AOD (35 and 30%, respectively). However, smoke (15%) and mineral dust (20%) cannot be neglected, especially during spring and summer. Results of numerical simulations indicate mean shortwave (SW) ARF for the whole Arctic (>70.5 o N) at the Earth's surface to be −4 W/m 2 for clear-sky and −1.3 W/m 2 for all-sky conditions, and at top of the atmosphere (TOA) −1.3 W/m 2 and -0.4 W/m 2, respectively. TOA ARF for anthropogenic and biogenic particles is only −0.1 W/m 2 for clear-sky and almost zero for all-sky conditions. For smoke and dust particles, SW ARF is very similar for both Earth's surface and TOA, as well as for clear-sky and all-sky conditions. For sea salt, SW ARF is the same at the surface and at TOA: 0.6 W/m 2 for clear-sky and −0.3 W/m 2 for all-sky conditions, because of negligible solar absorption. Cloud cover reduces surface cooling (direct clear-sky SW ARF) by a factor of 40% and shifts TOA SW ARF towards positive values. Highlights: Anthropogenic, biogenic, and sea salt particles are the most important aerosols in the Arctic. The total aerosol radiative forcing in the Arctic (>70.5 o N) is −0.4 W/m 2 for all-sky conditions. Anthropogenic aerosol radiative forcing is almost zero for all-sky conditions. Clouds reduce clear-sky aerosol radiative forcing by about 40%.